Proporsi Potongan Utama Komersial Karkas (Primal Cut) Pada Sapi Brahman Cross - Amri, Ulil (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The experiments was conducted to find proportion of primal cut on Brahman Cross Carcass. The experiment was conducted for 6 months in Slaughter house PT.SampiCo Adhi Abbatoir Cibitung BekasiÂ WestÂ Java.Â AÂ hundredÂ fortyÂ nineÂ (importedÂ fromÂ Australia)Â castratedÂ BrahmanÂ CrossÂ cattle (steer) were used with 1.5 up to more than 4 years of age and 379 â€“ 622 kg of body weight. The design was randomized block completely design in 3 x 4 factorial design with 3 feedlots and 4 group of body weight and was analysed following GLM procedure with median of smallest quadrat (SAS, 1985 and Montgomery,Â 1991).Â TheÂ studyÂ showedÂ thatÂ thereÂ was noÂ significantÂ onÂ primalÂ cutÂ weightÂ andÂ itsÂ percentageÂ amongÂ feedlot.Â IncreaseÂ bodyÂ weightÂ significantlyÂ increasedÂ weightÂ ofÂ primalÂ cutÂ butÂ no proportion of primal cut.Â